Effects of different negative pressure cupping interventions on inflammatory response and motor function recovery in delayed onset muscle soreness - Song, Xu; Ma, Teng; Cui, XianYou (Frontiers in Sports and Active Living, 2025)
IntroductionThis study examined the impacts of different negative pressure cupping therapies (NPCT) on pain relief, functional recovery, and inflammatory regulation in delayed onset muscle soreness (DOMS) after high-intensity exercise, with the aim of clarifying the dose-effect relationship.MethodsIn this study, 55 healthy male participants aged 18–25 were selected and divided into 5 groups: the control group (CTR; n = 11) and NPCT groups at different levels (−25 kPa, −35 kPa, −45 kPa, and −55 kPa; n = 11 in each group). A high-intensity protocol, which included 6 sets of lunges, squats, and squat jumps, was adopted to induce DOMS in the quadriceps femoris. Immediately after the exercise, the DGN-6 vacuum device was used for a 10 min NPCT treatment. The research outcomes included visual analog scale (VAS) pain scores, lower extremity explosive strength tests (30-meter sprint and standing long jump), joint range of motion (ROM), and serum biomarkers [CK, LDH, and inflammatory cytokines (IL-6, TNF-α, and Hsp27)]. These were assessed at the baseline and 24 h after the intervention.ResultsNPCT groups exhibited significantly lower VAS scores than the CTR group (−55 kPa: 1.57 ± 0.79 vs. 6.14 ± 0.69; P < 0.05), and the efficacy was pressure-dependent (−55 kPa > −4 kPa > −35 kPa; P < 0.01). Functional recovery was significantly improved in NPCT groups (30-meter sprint: 0.27 s; standing long jump: 0.08 m; P < 0.01). Knee ROM increased by 5.71° at −55 kPa and 6.43° at −45 kPa (P < 0.05). Biochemically, CK/LDH levels normalized in −45 kPa and −55 kPa groups (P < 0.05). Meanwhile, the levels of IL-6 and TNF-α decreased significantly (P < 0.05), and these changes were correlated with Hsp27 expression (r = 0.42–0.49; P < 0.05).DiscussionThese findings demonstrate that NPCT at pressures ranging from −45 kPa to −55 kPa is most effective in alleviating DOMS by enhancing hemodynamics and modulating the anti-inflammatory response, which supports its integration into post-exercise rehabilitation protocols. Clinical Trial Registrationhttps://www.chictr.org.cn/showprojEN.html?proj=263241, Chinese Clinical Trial Registry (ChiCTR) (Registration NO.: ChiCTR- 2500098071, 03/03/2025).